First documented pest outbreak of the herbivorous springtail Sminthurus viridis (Collembola) in Europe. (21st June 2016) - Crotty, F. V.; Fychan, R.; Benefer, C. M.; Allen, D.; Shaw, P.; Marley, C. L.
Abstract: Sminthurus viridis (Collembola: Sminthuridae) is a native of grasslands across Europe and feeds preferentially on clover ( Trifolium spp.) and lucerne ( Medicago sativa ), although its abundance does not normally reach damaging pest levels (as occurs in Australasia). This research note describes the first quantitative assessment of a pest outbreak of this springtail in Europe, which occurred within an existing experiment investigating the effects of cultivation practices on forage establishment. Using sticky traps to assess the incidence of S. viridis, we found a significant outbreak consisting of catches that were 10‐fold greater than background levels in nearby undamaged fields. Within the experimental area, lucerne established by direct drilling with herbicide had the highest incidence (105 (± 4·9) individuals per trap) compared to other treatments [79 (± 3·9)]. Results are discussed in terms of how cultivation practice may have imbalanced the ecosystem; for example, herbicide use may have diminished potential refugia for predators during forage establishment. This paper highlights the potential of a currently innocuous, widely established invertebrate to become present at damaging levels in agricultural crops.